Implementasi Keselamatan dan Keamanan Kapal Kapal yang Berlabuh (Drop Anchor) di Wilayah Perairan Batam - Awang Sasongko (Journal of Law and Policy Transformation, 2020)
The main purpose of this research is to understand the role of Syahbandar in the execution of shipping activities in sea freight in territorial waters according to "Act Number 17 of 2008" about shipping in Indonesia. The formulation of the problem consists of: (1) What is the minimum operating standard that must be owned by a ship that is anchored ? ; (2) Who has the highest authority in maintaining the safety and security of anchored ship ? ; (3) Has "Act Number 17 of 2008" been implemented correctly ? The method used in the research is juridical-sociological approach in the form of field survey and direct interviews with Stakeholder. The type of data used in the research is descriptive analysis method to solve the problem at hand.